Mechanisms of the intensification of the upwelling-favorable winds during El Nino 1997-1998 in the Peruvian upwelling system - Chamorro, A (2018)
This research is part of A. Chamorro’s PhD thesis, funded by the fellowship from CIENCIACTIVA/CONCYTEC-PERU at the University Pierre and Marie CURIE of Paris, France. It is also part of the IDB project PE-G1001/PE-T1297 (Adaptation to Climate Change of the Fishery Sector and Marine-Coastal Ecosystem of Peru), and it is a contribution to the cooperative agreement between the Instituto del Mar del Perú (IMARPE) and the Institut de Recherche pour le Developpement (IRD), the LMI DISCOH and JEAI EMACEP. The simulations were performed on the supercomputer Curie from the GENCI at the CEA (projects x2014011140, x2015011140 and x2016011140). Francois Pinsard and Sebastien Masson are acknowledged for their help in the making of lateral boundary forcing for the regional atmospheric model. Francis Codron, Clémentine Junquas, and lab colleagues from LMOECC at IMARPE are acknowledged for useful discussions.